In Vitro Effects of Different Combinations of Phytohormones on Callus Induction from Different Explants of Cabbage Brassica Oleracea Var. Capitata L. Seedlings - Hasan, Alaa. M.; ElKaaby, Ekhlas. A.J.; AL-Jumaily, Rakad. M.Kh. (Iraqi Journal of Science, 2021)
The leading purpose of this work is the development of efficient culture conditions to induce calli from cabbage (Brassica oleracea var. capitata L.) under in vitro conditions. The mature seeds were surface sterilized with combinations of different concentrations of ethanol and NaOCl in different time durations and were germinated on MS basal medium. The results revealed that the best sterilization method of cabbage seeds was by using 70% ethanol for one minute, followed by 15 min in 2% (NaOCl). Seedlings were used as donor sources for hypocotyls, cotyledon leaves, true leaves, and shoot tip explants. These explants were cultured on different combinations of cytokinins (TDZ, BAP, Ad) and auxins (IAA, NAA, 2, 4-D) then implanted in Murashige and Skoog (MS) media. 4 weeks after culturing, a significant difference was found among the explants in response to plant hormones. The maximum percentage of callus induction (100%) was using the combinations of 1 BAP + 1 2, 4-D, 1 BAP + 1 NAA, and 1 BAP + 2 2,4-D mg. l-1. In addition, explants responses varied and the hypocotyls showed a superior result (85.71 %) as compared to other explants. For callus fresh weight, the combination of 0.22 TDZ + 79.9 Ad mg. l-1 had a significant effect, causing the highest fresh weight (0.2745g), while control treatment gave the lowest mean of 0.0066 g. Data showed that cotyledon explants were significantly superior in giving highest callus fresh weight with the mean of 0.1723 g. On the other hand, hypocotyl explants gave the lowest mean, reaching 0.1542 g.